2020
DOI: 10.1177/0033354920938006
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Associated Mortality in a Hot Climate

Abstract: Objectives Maricopa County, Arizona (2017 population about 4.3 million), is located in the Sonoran Desert. In 2005, the Maricopa County Department of Public Health (MCDPH) established a heat-associated mortality surveillance system that captures data on circumstances of death for Maricopa County residents and visitors. We analyzed 2006-2016 surveillance system data to understand the characteristics and circumstances of heat-associated deaths. Methods We classified heat-associated deaths based on International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Additional research is being undertaken to understand the relationships between vegetation cover and the most immediate mosquito-borne disease threat to Maricopa County, West Nile virus. Despite mosquito-borne disease risk, heat currently is a larger public health burden, with the deaths of 172 people in Phoenix in 2017 attributed to extreme heat [ 50 ], and with the burden expected to increase with climate change [ 51 ]. Additional analyses to determine the specific causal link between tree cover and Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is being undertaken to understand the relationships between vegetation cover and the most immediate mosquito-borne disease threat to Maricopa County, West Nile virus. Despite mosquito-borne disease risk, heat currently is a larger public health burden, with the deaths of 172 people in Phoenix in 2017 attributed to extreme heat [ 50 ], and with the burden expected to increase with climate change [ 51 ]. Additional analyses to determine the specific causal link between tree cover and Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence indicates that mortality risks may be lower among people who are heat-acclimated. In a study of heat-related deaths in Maricopa County, Arizona, researchers found that non-Arizona residents were 5 times more likely to have an outdoor heat-related death [33]. Potentially, a similar phenomenon is occurring among people who become acclimated to the prison environment.…”
Section: Plos Onementioning
confidence: 99%
“…However, new momentum especially around energy and climate justice may soon close this gap. One key step is the increasing attention paid, including among government sources, to tracking 'energy insecurity' above and beyond fuel assistance 64,65,66 . As a concept that attempts to highlight the underlying structures producing hardship, 'energy insecurity' does have potential as a politicizing notion as seen with food and housing insecurity.…”
Section: Procedural Justicementioning
confidence: 99%